An overview on saffron, phytochemicals, and medicinal properties - Gohari, Ahmad Reza; Saeidnia, Soodabeh; Mahmoodabadi, Mahdie Kourepaz (Pharmacognosy Reviews, 2013)
Saffron is the most valuable medicinal food product because of its importance in Iran’s agricultural economy. The dried stigmas of the plant Crocus sativus (Iridaceae) are processing to produce saffron as a well‑known spice which has some other importance in pharmaceutics, cosmetics, perfumery, and textile dye‑producing industries. Recently, reports about the pharmacological activity of this plant increase its importance in the world. The world’s annual saffron production is estimated around 300 tons per year (Iran produces 76% of total) and also saffron is considered to be the most expensive spice in the world; hence, there are efforts for its artificial production or defraud. Therefore, the quality conservation of saffron needs to certify in the international trade market following international ISO or the Food and Drug Administration (FDA) criteria and standards. In this paper, the recent (or sometimes less documented) reports on phytochemistry, pharmacology, and standard methods for quality evaluation of saffron, as a medicinal food spice, from field cultivation to market are reviewed.
Keywords: Crocus sativus; Iridaceae; phytochemistry; saffron; standardization